Anterior cingulate cortex activity as a candidate biomarker for treatment selection in social anxiety disorder. Issue 3 (11th May 2018) - Frick, Andreas; Engman, Jonas; Wahlstedt, Kurt; Gingnell, Malin; Fredrikson, Mats; Furmark, Tomas
Summary: We aimed to identify biomarkers to guide the decision to add selective serotonin reuptake inhibitors (SSRI) to psychological treatment for social anxiety disorder (SAD). Forty-eight patients with SAD underwent functional magnetic resonance imaging and collection of clinical and demographic variables before treatment with cognitive–behavioural therapy, combined on a double-blind basis with either escitalopram or placebo for 9 weeks. Pre-treatment neural reactivity to aversive faces in the dorsal anterior cingulate cortex (ACC), but not clinical/demographic variables, moderated clinical outcomes. Cross-validated individual-level predictions accurately identified 81% of responders/non-responders. Dorsal ACC reactivity is thus a potential biomarker for SAD treatment selection. Declaration of interest: None.